Abrasive wearproofness of alloyed steels / V.I. Dvoruk, S.S. Belekh // Problems of Tribology. – 2012. – № 1. – Р. 14-19. - Дворук, В.І.; Бєлих, С.С. (Problems of Tribology, 2014)
The law of accordance is set between a reological parameter and abrasive wearproofness of alloyed steels of different structural classes after heat treatment in the conditions of wear the fastened abrasive which specifies on the necessity of application reological-kinetic approach/